Medical crowdfunding for cancer patients seeking fertility treatments: a cross-sectional analysis - Robyn A. Frankel, M.D.; Victoria Timmel, M.D.; Alexandra Peyser, M.D.; Baruch Abittan, M.D.; Christine Mullin, M.D.; Randi H. Goldman, M.D. (F&S Reports)
Objective: To explore the use of crowdfunding among patients with cancer seeking funding to offset the cost of fertility treatments. Design: Cross-sectional analysis of campaigns initiated on a single popular crowdfunding website, GoFundMe, for the purpose of subsidizing fertility treatments in patients with cancer from April to May 2022. Subjects: Patients utilizing crowdfunding campaigns to subsidize fertility treatments for either themselves or a partner with a cancer diagnosis. Campaigns unrelated to both cancer and fertility treatment coverage were excluded. Exposure: Not applicable. Main Outcome Measures: Dollar amount requested; amount and percent of goal obtained; top donation amount; number of donors or comments; geographic location; and cancer diagnosis. Chi-squared analyses and ANOVA statistics were used to characterize prevalence of geographic locations represented and differences in amount of financial support, respectively. A P<.05 was considered statistically significant. Results: A total of 1,195 campaigns were collected, spanning all regions of the United States and reflecting 23 different cancer diagnoses. The majority of campaigns resulted from breast (36.0%), lymphoma (10.6%), ovarian (7.1%), testicular (6.0%), or cervical (5.4%) cancer diagnoses. The average amount of funding requested across all campaigns was $31,390, with an average of $12,317 raised per campaign. More campaigns were initiated in Southern and Western regions of the United States compared with Northeastern and Midwestern (P<.001). However, Northeastern campaigns raised more money (P=.001), came closer to reaching their goals (P=.03), and gained more social support, as evidenced by number of donors (P<.001) and comments (P=.04). No statistically significant differences in financial or social outcomes were noted among campaigns when stratified by cancer type. Conclusion: Patients with cancer who desire or require fertility treatments often face tremendous financial and social difficulties. Our results suggest a higher financial burden on patients with cancer in Southern and Western states, despite being less likely to reach financial goals or obtain as much social support as Northeastern counterparts. Overall, the majority of campaigns did not meet their financial goals.